Observations of western gray whales by ship-based whalers in the 19th century - Reeves, Randall R.; Smith , Tim D.; Josephson , Elizabeth A. (J. Cetacean Res. Manage., 2023)
Animals belonging to the small, endangered population of western gray whales (Echrichtius robustus) are observed today primarily during the summer open-water season in feeding areas off the northeastern coast of Sakhalin Island, Russia. The migration route(s) and wintering area(s) used by this population are largely unknown. Gray whales once had a fairly extensive distribution in the Sea of Okhotsk but little detailed information has been published on when and where they occurred. Open-boat, ship-based whalers from the United States and a few other countries conducted an intensive hunt for bowhead whales (Balaena mysticetus) and North Pacific right whales (Eubalaena japonica) in the Sea of Okhotsk from the 1840s to 1870s. According to entries in voyage logbooks, the American whalers regularly encountered (and sometimes hunted) gray whales in the far northeastern corner of the Okhotsk Sea (Shelikhov Bay, Gizhiginskaya Bay and Penzhinskaya Gulf) between early May-late August. They also observed gray whales in summer along the northern coast of the sea (especially Tauskaya Bay), around the Shantar Islands, in Sakhalin Bay, off Cape Elizabeth at the northern tip of Sakhalin Island and along the west coast of the Kamchatka peninsula. No evidence was found in the logbooks studied of gray whales (and indeed of whaling effort) off northeastern Sakhalin Island where most observations of gray whales occur in the present day.